1999
DOI: 10.1021/jm980514x
|View full text |Cite
|
Sign up to set email alerts
|

Homology Modeling of Gelatinase Catalytic Domains and Docking Simulations of Novel Sulfonamide Inhibitors

Abstract: Three-dimensional models for the catalytic domain of gelatinases (MMP-9 and -2) have been constructed based on the X-ray crystal structure of MMP-3. Conformations of the loop segment which forms the bottom half of the S1' subsite but shows conformational diversity among the crystal structures of other MMPs have been explored by simulated annealing of each gelatinase model complexed with two highly potent "probe" inhibitors. Representative catalytic domain models have been selected for each gelatinase from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 29 publications
0
55
0
Order By: Relevance
“…To be an effective inhibitor of MMPs, the molecule requires a functional group (such as carboxylic acid, hydroxamic acid, or sulfhydryl) capable of chelating the active-site zinc (II) ion [28]. To improve selectivity these inhibitors are substituted with side chains which interact with specific subsites and undergo effective van der Waals interactions [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be an effective inhibitor of MMPs, the molecule requires a functional group (such as carboxylic acid, hydroxamic acid, or sulfhydryl) capable of chelating the active-site zinc (II) ion [28]. To improve selectivity these inhibitors are substituted with side chains which interact with specific subsites and undergo effective van der Waals interactions [33].…”
Section: Resultsmentioning
confidence: 99%
“…The S1' subsite (important pocket of MMPs) for the gelatinases is relatively deeper than for other subtypes and is targeted to obtain highly selective inhibitors. Therefore a sulfonamide group is incorporated in the inhibitor to improve the enzyme-inhibitor binding, not only by forming hydrogen bonds to the enzyme but also by properly directing the hydrophobic substituent to the S1' subsite and enabling it to plunge in deeply [28]. The substances 2-(4'-iodo-biphenyl-4-sulfonylamino)-3-(1H-indol-3-yl)-propionic acid, 2-(4'-iodo-biphenyl-4-sulfonylamino)-3-(1H-indol-3-yl)-propionamide and their iodine-123 analogues are developed from structure-activity data of compounds [10,29] with low nanomolar IC 50 potencies for gelatinases.…”
Section: Introductionmentioning
confidence: 99%
“…The S1' subsite for the gelatinases is relatively deeper than for other subtypes and is targeted to obtain highly selective inhibitors. A sulphonamide group is incorporated in the inhibitor to improve the enzyme-inhibitor binding not only by forming hydrogen bonds to the enzyme but also by properly directing the hydrophobic substituent to the S1' subsite and enabling it to plunge in deeply (Kiyama et al, 1998). The biphenyl function is incorporated to improve selectivity towards gelatinases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we synthesized the sulfonamide derivatives of pyroglutamate (6a), proline (7a), and thiazolidine (8a) since several literature data reported aryl-sulfonamide substituents to be the most favorable ones. 25 All novel compounds were synthesized (Scheme 3-6) and tested against gelatinases (Table 2). SAR analysis suggested that the introduction of a polar group, such as a carbonyl moiety at Y, maintaining a methylene group at Z position, strongly increases the inhibitory potency (i.e., 1a vs 2a; 5a vs 3a).…”
Section: Hit To Leadmentioning
confidence: 99%